Enriching Students’ Vocabulary Through Spelling Bee Game at The First Grade of SMP Negeri 4 Tondano - Labangka, Eva Silfana; Maru, Mister G.; Sabudu, Delli (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2025)
The purpose of this study was to determine whether or not using the Spelling Bee Game can enrich pupils’ vocabulary. This research was delimited on the teaching vocabulary particularly noun, utilising the Spelling Bee Game in the first grade of SMP Negeri 4 Tondano. The methodology used for this examine was quantitative. Furthermore, This study used a pre-experimental design with a single group doing both pre- and post-testing and the first grade students of SMP Negeri 4 Tondano which consisted 20 students were the subject of this study. In this study, there were 20 numbers for each test given to students. The result of our examine revealed that the average score in the post-test was more elevated (86,25) than average score of pre-test (43,5). The usage of the Spelling Bee Game can enrich pupils’ vocabulary, according to the result.